Peran Asuransi Syariah dalam Menguatkan Islamic Entrepreneurship Berbasis Halal Protection: Pengabdian - Soeharjoto Soeharjoto; Husna Leila Yusran; Sumiyarti; Debbie Aryani Tribudhi; Deni Mukti Hidayat; Adi Rosyadi; Teguh Supriyadi; Saiful Ali (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Low insurance literacy, especially Sharia insurance, poses a challenge in raising public awareness about the importance of risk protection. This is particularly true for young people who are currently or will be starting businesses. Aims of this community service activity is to increase literacy and awareness of sharia insurance among students at Global Cahaya Nubuwwah Insani (GCNI), an Islamic Entrepreneurship Boarding School in Purwakarta, West Java. This activity was conducted using an extension method that integrated Sharia insurance literacy with entrepreneurship education. The results of the activity showed an increase in students' understanding of the basic concepts of Sharia insurance, the differences between conventional and Sharia insurance, and the compatibility of Sharia insurance with Islamic principles, linked to entrepreneurship. This finding aligns with the concept that value-based financial literacy can shape more responsible and blessed economic and financial attitudes and behaviors. Sharia insurance literacy with a case study approach on Askrida Sharia Insurance has equipped students to better understand business risk management from an early age, so that their businesses are not solely profit-oriented, but sustainable for the common good.This activity proves that insurance literacy integrated with the values of the Quran and Hadith is effective in raising awareness about insurance from an early age.